Sex Differences in Demographic and Pharmacological Factors in Alzheimer Patients With Dementia and Cognitive Impairments - Coker-Ayo, Oreoluwa O.; Nathaniel, Samuel I.; Poupore, Nicolas; Bailey-Taylor, Melissa J.; Roley, Laurie Theriot; Goodwin, Richard L.; McPhail, Brooks; Russ-Sellers, Rebecca; Nathaniel, Thomas I. (Frontiers in Behavioral Neuroscience, 2022)
Objective: The current study investigates gender differences associated with pharmacological and demographic characteristics in Alzheimer patients (AD) with dementia (ADD) or mild cognitive impairment (MCI). Method: A retrospective analytical approach was used to analyze data from 45,696 AD patients with MCI or ADD. The univariate analysis was used to determine differences in demographic, and pharmacological characteristics for men and women ADD and MCI-AD patients. Multivariate analysis was used to predict specific pharmacological and demographic factors that are associated with men and women MCI and ADD patients. Result: In the adjusted analysis for men, Hispanics [0.166,0.020 – 1.355, P=0.094] or African Americans[ OR=2.380, 95% CI ,2.120 – 2.674, P<0.001], were more likely to have MCI-AD and be treated with galantamine [OR=0.559, 95% CI, 0.382 – 0.818, P=0.003], donepezil[OR=1.639, 95% CI,1.503 – 1.787, P<0.001], rivastigmine[ OR=1.394, 95% CI ,1.184 – 1.642, P<0.001], olanzapine[OR=2.727, 95% CI,2.315 – 3.212, P<0.001], risperidone[OR=2.973, 95% CI ,2.506 – 3.526, P<0.001],present with increasing age[1.075,1.071 – 1.079, P<0.001], and are on tobacco use [OR=1.150, 95% CI ,1.054 – 1.254, P=0.002]. For women, buspirone [OR=0.767, 95% CI,0.683 – 0.861, P<0.001] and a history of alcohol (ETOH) use [OR=0.484, 95% CI, 0.442 – 0.529, P<0.001] were associated with MCI-AD. Increasing age [OR=1.096, 95% CI,1.093 – 1.100, P<0.001], donepezil[OR=2.185, 95% CI,2.035 – 2.346, P<0.001], memantine [OR=2.283, 95% CI,2.104 – 2.477, P<0.001] aripiprazole [OR=1.807, 95% CI,1.544 – 2.113, P<0.001] olanzapine [OR=2.289, 95% CI, 1.986 – 2.640, P<0.001] risperidone [OR=2.548, 95% CI, 2.246 – 2.889, P<0.001] buspirone [OR=0.767, 95% CI, 0.683 – 0.861, P<0.001] escitalopram [OR=1.213, 95% CI,1.119 – 1.315, P<0.001] African Americans [OR=1.395, 95% CI,1.268 – 1.535, P<0.001] and tobacco use [OR=1.150, 95% CI,1.073 – 1.233, P<0.001] were associated with ADD. Conclusion: Our findings reveal that MCI-AD patients were more likely to be Hispanics or African American men and more likely to be treated with rivastigmine, olanzapine and citalopram. African American women were associated with ADD and more likely to be treated with buspirone and presented with a history of ETOH. This finding suggests the need for a pharmacological treatment approach encompassing gender-sensitive strategies for MCI-AD and ADD patients.